The efficacy and safety of dopamine versus norepinephrine in management of paediatric septic shock - Chaurasiya, Dharmendra; Chhabra, Kawalpreet; Sethi, Anuj S.; Chaurasiya, Omshankar (International Journal of Contemporary Pediatrics, 2024)
Background: Septic shock is one of most common cause of death in pediatric patients. The optimum septic shock vasopressor support strategy is currently debated. This study was performed to evaluate the efficacy and safety of norepinephrine (NE) and dopamine (DA) as the initial vasopressor in pediatric septic shock patients. Methods: A prospective, randomized, clinical trial was carried out between January 2022 to January 2023 in a pediatric intensive care unit comparing DA with NE as the initial vasopressor in fluid-resuscitated 100 pediatric patients with septic shock. Normalization of blood pressure was taken as end point. If the maximum dose of the initial vasopressor was unable to attain the hemodynamic goal, then another vasopressor agent was added. Patients were monitored for response and side effect. Results: DA had a mortality of 50% as compared to 40% in NE. Arrhythmias occurred in 27.5% cases in DA group and 8.33% cases in NE group. There was a significantly greater incidence of sinus tachycardia with DA (12.5%) than NE (5%). Conclusions: NE showed better efficacy than DA in pediatric patients with septic shock with lesser event of arrhythmias.